2001
DOI: 10.1021/ac000958c
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Multianalyte Detection with a Nanometer-Scale Pore

Abstract: It was recently shown that naturally occurring, genetically engineered or chemically modified channels can be used to detect analytes in solution. We demonstrate here that the overall range of analytes that can be detected by single nanometer-scale pores is expanded using a potentially simpler system. Instead of attaching recognition elements to a channel, they are covalently linked to polymers that otherwise thread through a nanometer-scale pore. Because the rate of unbound polymer entering the pore is propor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
218
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 181 publications
(220 citation statements)
references
References 26 publications
2
218
0
Order By: Relevance
“…This and previous work demonstrated that the lifetimes of polynucleotide transits are typically 1-10 s per base. 40,59,63,64 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This and previous work demonstrated that the lifetimes of polynucleotide transits are typically 1-10 s per base. 40,59,63,64 …”
Section: Resultsmentioning
confidence: 99%
“…40 These events were digitally recorded and the lifetime, amplitude, and pattern of the ssDNA-induced current blockades were measured. [59][60][61] A. Membrane and channel formation Solvent-free planar lipid bilayer membranes 62 were formed from diphytanoyl phosphatidylcholine ͑Avanti Polar Lipids, Inc., Alabaster, AL͒ in pentane ͑Burdick and Jackson, Muskegon, MI͒. The membranes were made on 50-120 m diameter holes in a 17 m thick Teflon partition that separates two identical Teflon chambers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the target DNA binds to its complementary sequence and takes longer to translocate than the other chains. Another analysis method has been implemented by Kasianowicz' group [12]. In this case, DNA sequences are first designed to bind with a given analyte and are then allowed to translocate.…”
Section: Nanopore Technologiesmentioning
confidence: 99%
“…Therefore, in practice, this is a superb equation to use. An example of mobility-size data fitting using the new mobility relation (12). Double-stranded DNA fragments in the 200 bp to 48 kbp range were used.…”
Section: A Universal Mobility Relation For Gel Electrophoresis?mentioning
confidence: 99%